Application of Automatic Fertilization Technology in Aquaponic Farming System Based on Internet of Things - Sarosa Castrena Abadi; Muhammad Nursyam Rizal; Suharyadi Pancono; Siti Aminah; Noval Lilansa; Cepi Ramdani (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Rural communities in Cibodas, East Bandung, face serious challenges in aquaponic farming practices, particularly in the uneven application of conventional fertilizers. This imbalance results in suboptimal crop quality, reducing the potential for agricultural productivity in the region. To overcome this obstacle, an innovative solution is needed in the form of an Internet of Things (IoT)-based automatic liquid fertilizer irrigation system. This system is designed to distribute fertilizer evenly to all plants, ensuring that each part of the plant receives adequate nutrients, and that fertilizer is applied efficiently. The use of this system not only increases the efficiency of farmers' work, but also contributes to improving the overall quality and quantity of crop yields. The stages of activities in the implementation of this community service are the development of an automatic liquid fertilizer irrigation system based on the Internet of Things (IoT), the application or implementation of the system, and finally the socialization of the use of the system. This community service activity is a series of student community service activities carried out in October 2024. The elements involved are the community of Cibodas Village, lecturers and students of Politeknik Manufaktur Bandung. As a result of this service activity, the community understands and can apply agricultural technology, in this case IoT-based automatic liquid fertilizer spraying technology with remote control. The liquid fertilizer spraying and watering system can increase the efficiency of time and energy. It is hoped that the technology that has been developed will be one of the effective solutions to the problem of uneven spraying of plant fertilizers.